Involvement of a chloroplast HSP70 heat shock protein in the integration of a protein (light-harvesting complex protein precursor) into the thylakoid membrane. - Yalovsky, S (1992)
Molecular chaperones, including those belonging to the 70-kDa family of heat shock proteins (HSP70), assist both the translocation of proteins across membranes and their assembly into oligomeric complexes. We purified a chloroplast HSP70 (ct-HSP70) and demonstrated that it plays a major role in the insertion of the precursor of the major light-harvesting complex of photosystem II (pLHCP; an integral membrane protein) into the thylakoids (the inner membranes of the chloroplast). Addition of the purified ct-HSP70 is necessary for efficient insertion of pLHCP into isolated thylakoid membranes. This activity of the purified ct-HSP70 is similar to that previously reported for the total stromal extract. When the chloroplast stromal extract is depleted of HSP70, a correlative reduction in the insertion activity of pLHCP is observed. The interaction between the ct-HSP70 and pLHCP involves physical association. The purified HSP70 acts directly on the membrane protein, presumably prevents its refolding, and thereby helps to maintain its competence for insertion into membranes.